Kinerja Guru dalam Meningkatkan Mutu Pendidikan Melalui Kurikulum 2013 di SD Negri Timpik 1 Tahun 2017 - Widagdorini, Hendrawati Niken; , Drs. Mulyadi Sri Kamulyan, S.H, M.Pd (2017)
This study aims to (1) reduce the performance of teachers in improving the quality of education through the 2013 curriculum in SD Negeri Timpik 01 the year of 2017; (2) to describe the teacher's efforts in improving the quality of education through the 2013 curriculum in SD Negeri Timpik 01 the year of 2017; And (3) to identify the obstacles of teachers in improving education through the 2013 curriculum in SD Negeri Timpik 01 the year of 2017. This research used qualitative descriptive method. Source of data obtained from transcripts from interviews conducted to Teachers and Principals of SD Negeri Timpik 01. Techniques of data collection using interview techniques, observation, and documents. Data analysis technique used is the data analysis phase by McMillan and Sally Schumacher. The results of this study are (1) the performance of teachers in improving the quality of education through the 2013 curriculum at SD Negeri Timpik 01 are as follows: (a) preparing teacher books and student books before the learning process; (b) understanding of student's books and teachers' (E) to increase students' learning interest, teachers apply reward and punishment systems, (f) teachers develop students' cognitive potential in learning, (e) to improve the students' learning interests, G) provide learning media and tools both real and LCD, and (h) prepare assessment instruments. (2) the efforts of teachers in improving the quality of education through the 2013 curriculum at SD Negeri Timpik 01 are as follows: (a) to conduct training in the form of curriculum training in 2013 and (b) teacher certification program. (3) teachers' obstacles in improving the quality of education through the 2013 curriculum in SD Negeri Timpik 01 are: (a) the learning is difficult for students, especially the lower classes, (b) the assessment in the curriculum of 2013 takes a lot of time for teachers, (c) According to their age and extent in the use of teachers and students 'books, (d) teachers' readiness to use less curriculum 2013, (e) teachers feel overwhelmed by authentic judgment.